Wrestling with the bottom line in medical education. Issue 10 (2nd August 2022) - Wiese, Anél; Bennett, Deirdre
Abstract : Wiese and Bennett advance the conversation about economic evaluation in health professions education by outlining its potential applications in pratice and research.